Production of a peptide composition with ACE inhibitory properties from green soybean - Saari, Nazamid; Ebrahimpour, Afshin; Hashim, Siti Nadia; Abdul Hamid, Azizah; Hanafi, Mohamad Ariff (2013)
The present invention pertains to a process for manufacturing a proteolysate with angiotensin converting enzyme (ACE)-inhibitory properties, and to the isolate produced according the method of the invention. Therefore, furthermore is provided a method of identifying ACE inhibitory peptides from the proteolysate of the invention. The invention also relates to the peptides isolated using the screening method and the ACE inhibitory proteolysate of the invention. The products of the invention are particularly useful for the treatment of cardiovascular diseases and thus can be used as medicines, or as food additives or supplements.